EFFECTS OF FERTILIZER MICRODOSING ON SOIL PHOSPHORUS AND SULPHUR AVAILABILITY TO SOLANUM MACROCARPON IN SOUTHWEST NIGERIA - Olatoberu, Francis; Oluwaponle, Adesewa; Akinremi, Omotayo; Idowu, Mary; Oyedele, Durodoluwa; Oladoye, Christianah; Ojo, Adekunle; Odunayo, Adebooye (Journal of Agricultural Sciences (Belgrade), 2025)
Solanum macrocarpon also known as egg-plant is an important indigenous vegetable. It is known for its medicinal, nutritional purposes, as a result, it plays a key role in income generation and subsistence in Nigeria. This study examined the effect of fertilizer rate and time of application on yield, determined the availability of soil P and S to S. macrocarpon. This was with a view to establish the optimum fertilizer rate and application time for S. macrocarpon production using microdosing technology in southwest Nigeria. The experiment was located at the derived savanna (Ogbomoso) and the rainforest (Ilesha) in southwest Nigeria. The treatments were arranged in a factorial combination and laid out in a split plot design with four replicates. The main plots were the fertilizer rate; 0, 20, 40, 60, and 80 (without organic fertilizer) kg N ha-1, the time of urea application (at planting and two weeks after planting) as sub-plot and S. macrocarpon was the test crops. Plant fresh weight, P and S uptake were determined at the first harvest. The data generated were subjected to analysis of variance (ANOVA) and the means separated using Duncan’s New Multiple Range Test at 5 % level of probability. The results showed that fertilizer rate at 20 kg N ha-1 produced significantly higher yields and uptake of P and S at the derived savanna (4.2 t ha-1) and at the rainforest (1.2 t ha-1). Application at two weeks after planting (2 WAP) produced higher yields (3.3 t ha‑1) at the derived savanna while the application at planting (AAP) produced highest (1.2 t ha‑1) at the rainforest. Although, the time of fertilizer application had no effect on the fresh yields and nutrient availability, this study concluded that 60 kg N ha -1 + 5 tons ha -1 was the optimum fertilizer combination for S. macrocarpon production in southwest Nigeria. Keywords: Solanum macrocarpon, phosphorus, sulphur, fresh weight, fertilizer, microdosing Rezime Solanum macrocarpon, poznat i kao patlidžan, važna je autohtona povrćarska vrsta. Značajan je zbog svojih lekovitih i nutritivnih svojstava, te igra ključnu ulogu u stvaranju prihoda i osiguranju egzistencije u Nigeriji. Ova studija je ispitivala uticaj doze đubriva i vremena primene na prinos, kao i dostupnost fosfora (P) i sumpora (S) u zemljištu za S. macrocarpon. Cilj je bio da se utvrdi optimalna doza đubriva i vreme primene za gajenje S. macrocarpon korišćenjem tehnike mikrodoziranja u jugozapadnoj Nigeriji. Eksperiment je sproveden u savanskoj zoni (Ogbomoso) i prašumskoj zoni (Ilesha) u jugozapadnoj Nigeriji. Tretmani su postavljeni u faktorskoj kombinaciji i raspoređeni u split-plot dizajnu sa četiri replikacije. Glavne parcele su sadržale različite doze đubriva: 0, 20, 40, 60 i 80 kg N po hektaru (bez organskog đubriva), dok je vreme primene ureje (pri sadnji i dve nedelje nakon sadnje) predstavljalo podparcele. S. macrocarpon je bio testirani usev. Sveža masa biljaka, unos P i S određeni su nakon prve berbe. Podaci su analizirani pomoću ANOVA-e, a srednje vrednosti su razdvojene Duncanovim novim multirange testom na nivou verovatnoće od 5%. Rezultati su pokazali da je doza od 20 kg N/ha dala značajno veće prinose i unos P i S u savanskoj zoni (4,2 t/ha), odnosno u prašumskoj zoni (1,2 t/ha). Primena đubriva dve nedelje nakon sadnje (2 WAP) rezultirala je većim prinosima u savani (3,3 t/ha), dok je primena pri sadnji (AAP) dala najbolje rezultate u prašumi (1,2 t/ha). Iako vreme primene nije imalo uticaja na svežu masu i dostupnost hraniva, studija je zaključila da je kombinacija 60 kg N/ha + 5 t/ha organskog đubriva optimalna za proizvodnju S. macrocarpon u jugozapadnoj Nigeriji. Ključne reči: Solanum macrocarpon, fosfor, sumpor, sveža masa, đubrivo, mikrodoziranje